Ethical issues raised in the care of the elderly during the SARS-CoV-2 pandemic and possible solutions for the future: a systematic review of qualitative scientific literature - Mohamed Amine Bouchlaghem; Zoé Estey-Amyot; Erika Ethier; Miruna Anohim; Marie-Laurence Ouellet-Pelletier; Lyse Langlois; Félix Pageau (BMC Medical Ethics)
Abstract Background The COVID-19 pandemic has led governments worldwide to make ethically controversial decisions. As a result, healthcare professionals are facing several ethical dilemmas, especially in terms of healthcare services provided to senior citizens. Thus, the aim of this review is to identify and categorize ethical dilemmas as well as propose solutions regarding health care services for elderly individuals. Methods A qualitative systematic review of the literature was undertaken in the first tier of the pandemic. All identified scientific and editorial articles published in English or French between December 2019 and October 2021 were included. An article was excluded if it was commercial, did not address an issue in the care of the elderly or present any qualitative data. Article eligibility was determined through a process of triangulation among three independent reviewers. Results Initially, 69 articles met our inclusion criteria and were selected for this review. These studies can be divided into 2 distinct categories: scientific articles (17 studies) and expert opinion articles (52 articles). However, due to the large quantity of qualitative data that was extracted, only the results from the scientific literature are presented here. The analysis of the data of 17 studies has allowed the emergence of 2 main themes of ethical dilemmas: 1) access to care (3 subthemes: A) triage decisions for admission, B) access to the intensive care unit and C) vaccine allocation) and 2) infection control decisions (2 subthemes: (D) isolation and E) autonomy). Our results also revealed 4 categories of potential solutions to the encountered ethical dilemmas, namely, optimal protocols, enhanced communication, caregiver support and technological assistance (virtual team-based, AI). Conclusions The ethical dilemmas that emerged from our results highlight the interest of a serious international discussion around the phenomena of ageism and its potential ethical implications for health care workers (be it under normal circumstances or exceptional circumstances such as those of a pandemic). We highly recommend that future research be undertaken to test the efficacy of the proposed solutions in providing age-friendly, dilemma-free health care and environments.